Gut microbiota and their derivatives in the progression of colorectal cancer: Mechanisms of action, genome and epigenome contributions - Awais Ahmad; Nasir Mahmood; Muhammad Ahtisham Raza; Zarina Mushtaq; Farhan Saeed; Muhammad Afzaal; Muzzamal Hussain; Hafiz Wasiqe Amjad; Hashim Mohammad Al-Awadi (Heliyon, 2024)
Gut microbiota interacts with host epithelial cells and regulates many physiological functions such as genetics, epigenetics, metabolism of nutrients, and immune functions. Dietary factors may also be involved in the etiology of colorectal cancer (CRC), especially when an unhealthy diet is consumed with excess calorie intake and bad practices like smoking or consuming a great deal of alcohol. Bacteria including Fusobacterium nucleatum, Enterotoxigenic Bacteroides fragilis (ETBF), and Escherichia coli (E. coli) actively participate in the carcinogenesis of CRC. Gastrointestinal tract with chronic inflammation and immunocompromised patients are at high risk for CRC progression. Further, the gut microbiota is also involved in Geno-toxicity by producing toxins like colibactin and cytolethal distending toxin (CDT) which cause damage to double-stranded DNA. Specific microRNAs can act as either tumor suppressors or oncogenes depending on the cellular environment in which they are expressed. The current review mainly highlights the role of gut microbiota in CRC, the mechanisms of several factors in carcinogenesis, and the role of particular microbes in colorectal neoplasia.